2006
DOI: 10.3164/jcbn.38.180
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Garcinia cambogia-Induced Impairment of Spermatogenesis and Meiosis-Activating Sterol Production in Rat Testis

Abstract: Summary Dietary supplements for body fat reduction have become popular, particularly in developed countries. Garcinia cambogia (GA) is one such supplement, and its active component is (−)-hydroxycitric acid ((−)-HCA), a competitive inhibitor of ATP citrate lyase, which is responsible for producing acetyl CoA from citric acid. Recently we have found that administration of (−)-HCA-containing GA markedly reduces testis weight in male Zucker obese rats. In particular, histopathological examinations revealed testic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…We have reported recently that the high dose of (−)-HCAcontaining GA ((−)-HCA levels; 102 mmol / kg diet or higher) causes potent testicular atrophy and toxicity in male rats [7], and suggested that (−)-HCA-mediated inhibition of ATP citrate lyase leads to diminished accumulation of T-MAS in rat testis [8], thus probably resulting in impairment of spermatogenesis. In the present study, we examined the effect of GA administration on safety with special reference to female reproductive organs in rats.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have reported recently that the high dose of (−)-HCAcontaining GA ((−)-HCA levels; 102 mmol / kg diet or higher) causes potent testicular atrophy and toxicity in male rats [7], and suggested that (−)-HCA-mediated inhibition of ATP citrate lyase leads to diminished accumulation of T-MAS in rat testis [8], thus probably resulting in impairment of spermatogenesis. In the present study, we examined the effect of GA administration on safety with special reference to female reproductive organs in rats.…”
Section: Discussionmentioning
confidence: 99%
“…In the former study, we focused the effect of GA administration on body fat accumulation using Zucker obese rats [7], and in the previous study, we examined the effect of GA administration on testicular toxicity in Fischer 344 (F344) strain rats [8]. Since the aim of the current study was to elucidate safety in female rats, we used rats of SD-IGS strain, a strain often used lately in toxicological study together with F344 strain, and a diet containing (−)-HCA at 154mmol /kg diet, the highest dose in the former study [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations